The Defect Structure Evolution in MgH2-EEWNi Composites in Hydrogen Sorption–Desorption Processes - Viktor N. Kudiiarov; Alan Kenzhiyev; Roman R. Elman; Nikita Kurdyumov; Ivan A. Ushakov; Andrei V. Tereshchenko; Roman S. Laptev; Mark A. Kruglyakov; Parvizi I. Khomidzoda (Metals)
This paper presents the results of the study of the composite based on magnesium hydride with the addition of nanosized nickel powder, obtained by the method of an electric explosion of wires. The obtained MgH2-EEWNi (20 wt.%) composite with the core-shell configuration demonstrated the development of a defect structure, which makes it possible to significantly reduce the hydrogen desorption temperature from 418 °C for pure magnesium hydride to 229 °C for hydride with the addition of nickel powder. In situ studies of the evolution of the defect structure using positron annihilation methods and diffraction methods made it possible to draw conclusions about the influence of the Mg2NiH0.3 and Mg2NiH4 phases on the sorption and desorption properties of the composite. The results obtained in this work can be used in the field of hydrogen energy in mobile or stationary hydrogen storage systems.